Discursive constructions of populism in opinion-based journalism: A comparative European study. (December 2021) - Thornborrow, Joanna; Ekstrom, Mats; Patrona, Marianna
Abstract: This study offers a contribution to current research on populism and the media by exploring the attribution of populism as a discursive label in editorials and opinion-based articles from France, Greece, Sweden and the UK. Taking a corpus-assisted, discourse analytic approach, we undertake a comparative, empirical analysis of the use of the terms 'populism/populist', focusing on the attribution of populist characteristics to political actors, parties and practices, and how these function in producing journalistic stance in relation to political populism as a phenomenon in 2017. We examine the patterns and variations in the range of salient semantic fields and metaphorically evaluative language identified across the corpus, and argue that there is strong evidence for the existence of a shared meta -language in relation to the conceptualization of populism and constructions of stance towards it, which nevertheless serves as a flexible resource for journalistic positioning in different socio-political contexts.